The impact of using humor in English lessons on student engagement and vocabulary recall in middle school classes - Baqoyeva , Nigina Nodirbek qizi; Sultonova , Maftuna Baxtiyorovna (The Lingua Spectrum, 2026)
This study explores the impact of using humor in English lessons on student engagement and vocabulary recall in middle school classes. In modern language teaching, creating a positive and motivating learning environment is essential for effective learning, especially for young learners who may feel anxious or less confident when using a foreign language. Humor is considered one of the effective strategies that can make English lessons more interesting, interactive, and memorable. The research focuses on how humor influences students’ participation in classroom activities and their ability to remember new vocabulary. It also examines the role of humor in reducing anxiety, increasing students’ confidence, and encouraging them to communicate more actively in English. The study highlights that appropriate humor can help teachers build a friendly classroom atmosphere and strengthen the relationship between teachers and students. The findings of the study show that the use of humor in English lessons improves student engagement and helps learners retain vocabulary more effectively. The study suggests that humor can be used as an effective teaching tool in middle school EFL classrooms when it is relevant, respectful, and connected to the lesson content.